Life in the country house in Georgian Ireland - McCarthy, Patricia 1947- (The Paul Mellon Centre for Studies in British Art by Yale University Press, 2019)
"For aristocrats and gentry in 18th-century Ireland, the townhouses and country estates they resided in were carefully constructed to accommodate their cultivated lifestyles. Based on new research from Irish national collections and correspondence culled from papers in private keeping, this publication provides a vivid and engaging look at the various ways in which families tailored their homes to their personal needs and preferences. Halls were designed in order to simultaneously support a variety of activities, including dining, music, and games, while closed porches allowed visitors to arrive fully protected from the country's harsh weather. These grand houses were arranged in accordance with their residents' daily procedures, demonstrating a distinction between public and private spaces, and even keeping in mind the roles and arrangements of the servants in their purposeful layouts. With careful consideration given to both the practicality of everyday routine and the occasional special event, this book illustrates how the lives and residential structures of these aristocrats were inextricably woven together." --Provided by publisher
Keywords: Sozialgeschichte 1720-1840; Geschichte 1720-1840; Architektur; Herrenhaus; Landhaus; Ikonographie; Palladianismus; Landleben; Irland; Country homes / Ireland; Country life / Ireland; Domestic space / Ireland; Ireland / Social conditions / 18th century; Ireland / Social conditions / 19th century; Country homes; Country life; Domestic space; Social conditions; Ireland; 1700-1899; History